Beam Deflections and Stresses During Lifting - R.H. Plaut, C.D. Moen and R. Cojocaru (Engineering Journal, 2012)
The behavior of horizontally curved beams during lifting is analyzed. The beams are circularly curved, doubly symmetric, prismatic and linearly elastic, and they are suspended at two symmetric locations. The two cables lifting the beams may be vertical or inclined symmetrically. Numerical results are presented for steel I-beams. Weak-axis and strong-axis deflections, roll angle and cross-sectional twist, internal forces, bending and twisting moments, and longitudinal stresses are calculated using newly derived analytical solutions implemented as a freely available spreadsheet at http://www.moen.cee.vt.edu/. Lifting locations along the beam that minimize displacements and stresses are identified.